Prilaku Agresif Santri di Pondok Pesantren Putri Annuriyah Wonocolo Surabaya - Latifatu Zuhriya; Misbakhus Surur (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2021)
Aggressive behavior is behavior that is intended to hurt another person, either physically or psychologically. Adolescence is a phase of growth that is prone to aggressive behavior. This is caused by several basic factors. Namely anger, changes in biological conditions, generation gaps, and the environment. The design of this research is qualitative with a descriptive approach, thus researchers can review more deeply about the subject by understanding in detail the subject. The description of the aggressive behavior of a santri is sarcastic friends, speaking in a loud tone, speaking loudly, speaking dirty, and refusing to speak. As for the factors in aggressive behavior is the learning process in the form of seeing events, the environment in the form of room temperature, and the community environment in the form of people around the subject. The results of this study indicate that the subject is classified as a person who behaves aggressively in the form of verbal aggression, the subject is also classified as a person who has problems in boarding schools and at school in the form of leaving the boarding school without permission, and making noise in class.